ANALISIS SENSITIVITAS ETIS MAHASISWA (STUDI KASUS PADA UNIVERSITAS SWASTA DI SEMARANG - Diska Anastasia Putri, 10.05.52.0075; Kartika, Andi (Students Journal of Accounting and Banking, 2014)
This research aims to examine whether there are differences between the ethical sensitivity of accounting students and students of management, accounting students and students of management accounting man against unethical activity in the academic environment. Besides, this study also tested whether students are more tolerant of unethical behavior would be more cynical. This study was performed using experimental design, with purposive sampling technique in which researchers can classify research subjects in the group 2. 2 Distribution of the first group is a group of accounting students and students of management, and the second group is the student division of male and female students majoring in accounting. Data obtained by conducting a study of 191 college students and 182 students of management accounting. Data were analyzed by using different test independent sample t test or Mann Whitney test. The results showed that the hypothesis of the four hypotheses exist, there are two hypotheses in this study were acceptable. Accepted hypothesis is as follows: the difference obtained unethical behavior and cynical attitudes are significant in accounting and management students.Keywords: Sensitivity Ethics, cynical / Cynicism